Developing an accountability disclosure index for Malaysian state Islamic religious concils (SIRCS): quantity and quality / Rosnia Masruki, Khaled Hussainey and Doaa Aly - Masruki, Rosnia; Hussainey, Khaled; Aly, Doaa (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
This study aims to develop Accountability Disclosure Index (ADI) for Malaysian State Islamic Religious Councils (SIRC), concerning both quantity and quality. In this case, the quality of disclosure items was developed based on the qualitative characteristics, which rely on the International Financial Reporting Standards (IFRS) conceptual framework; namely, relevance, faithful representation, understandability, comparability and timeliness. Each characteristic is scored based on the ‘benchmark’ score, ranging from poor (1) to excellent (5). However, some of the characteristics have been modified to contextualize the SIRC study setting. Both quantity and quality of disclosure items index might contribute to a methodology for analysing and evaluating annual reports. Results show fifty-seven items of disclosure information, which were regarded by stakeholders relevant to be disclosed by SIRC. Indeed, all these disclosure items should be disclosed in SIRC annual reports, so as to meet the expectations of a wide range of stakeholders. With regards to the quality of disclosure, two different sets of qualitative characteristics for non-financial and financial statement disclosure were designed. All five qualitative characteristics were adapted to measure the quality of financial disclosure, whereas for non-financial disclosure, 'timeliness' was dropped due to the voluntarily nature of non-financial disclosure.